Vowel Formants of Czechoslovak Radio Announcers from 1970 to 1989 - Pořízka, Petr; Kopečková, Michaela (Bohemica Olomucensia, 2018)
The paper focuses on the analysis of the vocal articulations of twenty announcers (10 women and 10 men) from the Czech (Czechoslovak) Radio. We used for this purpose the material of so called NAKI sound database (data come from 1970 to 1989). We focused specifically on the quality of czech vowels: Both short and long monophtong vowels were analyzed and the first two formant frequencies (called F1 and F2) were measured. We compared those two formant frequencies with the reference values of the Czech vowels. The results of this analysis are interpreted and suplemented by the data tables and charts.
Keywords: NAKI database; Czech radio broadcasting; vowel(s); formant(s); vowel plots; descriptive statistics; quantitative analysis